Preparation method of coal gasification slag loaded nickel-based catalyst and application of coal gasification slag loaded nickel-based catalyst in depolymerization of lignin or derivatives thereof

By preparing catalysts on the gas -based dregs, the problem of low efficiency of gas -based slag and lignin utilization efficiency in existing technologies has been solved, and the efficient, selective and environmental protection technology of lignin catalysis can be achieved.

CN119346115APending Publication Date: 2025-01-24CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411451128.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize coal gasification slag and lignin, and in the catalytic hydrogenolysis reaction of lignin, excessive hydrogenation of aromatic products is difficult to avoid.

Method used

By loading nickel-based compounds on coal gasification slag, a high-performance coal gasification slag-supported nickel-based catalyst is prepared and applied in the catalytic depolymerization process of lignin or its derivatives, utilizing the medium specific surface area and appropriate pores of the catalyst. structure, inhibits the hydrogenation of aromatic products.

Benefits of technology

The efficient utilization of coal -based and biomass -based waste is realized, and high -selectivity and high -efficiency aromatic products are prepared, and the process is green and environmentally friendly, and has economic and performance advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346115A_ABST
    Figure CN119346115A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a coal gasification slag loaded nickel-based catalyst and application of the coal gasification slag loaded nickel-based catalyst in depolymerization of lignin or derivatives thereof. Completely dissolving the nickel-based compound in a beaker; adding CGS, and continuously stirring to ensure that the metal precursor is highly dispersed on the carrier; sealing the mixed solution with tin foil paper, dipping in a vacuum drying oven at room temperature, and drying; and uniformly grinding the obtained blocky solid by using a mortar, calcining and reducing the solid powder, introducing N2 into a pipe, exhausting air in a reactor, calcining, switching N2 into H2, reducing at the same volume flow rate and the same temperature, switching H2 into N2 after reduction, naturally cooling, and carrying out vacuum drying to obtain the coal gasification slag loaded nickel-based catalyst. According to the method, the coal gasification slag is used as a carrier to synthesize the high-performance catalyst, and the catalyst is excellent in application effect when applied to depolymerization of lignin or derivatives thereof, is green and environment-friendly, and has efficient economic and performance advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a method for preparing a coal gasification slag-loaded nickel-based catalyst and application thereof in the depolymerization of lignin or its derivatives. Background Art

[0002] A large amount of coal gasification slag is inevitably produced during the coal gasification process, and the annual output of coal gasification slag is huge. In China, the annual output of coal gasification slag is hundreds of millions of tons. However, coal gasification slag has not been well utilized. At present, the main disposal methods of coal gasification slag are landfill or stacking, which will cause soil pollution and waste of resources. As a solid waste, how to achieve efficient recycling of coal gasification slag has become a research hotspot in the direction of coal-based solid waste utilization. During the generation process, coal gasification slag produces partial pore structure on the surface through high-temperature gasification, and the unburned carbon in the gasification slag can also load certain metals. Therefore, coal gasification slag has potential application advantages in being used as a catalyst carrier.

[0003] Lignin is a waste generated in the pulping and papermaking process, and the rational utilization of waste (or biomass-based) lignin is also a hot topic of concern for researchers. At present, the main methods for lignin depolymerization are: oxidation, pyrolysis, hydrogenolysis and hydrodeoxygenation. Among them, catalytic hydrogenolysis, as a green and efficient method, has been widely used in lignin depolymerization reactions. The study of using catalysts prepared with coal gasification slag as raw materials for catalytic conversion of lignin can greatly realize the effective utilization of coal-based and biomass-based wastes. At present, coal gasification slag has not been used for catalytic hydrogenolysis of lignin. This research process has significant application prospects in effectively solving waste problems. And this research can be applied to commercial production processes on a large scale in the later stage.

[0004] Lignin contains abundant CO bonds, and high value-added aromatic products can be obtained by cracking the CO bonds in lignin. The phenols obtained by converting lignin and its model compounds are easily hydrogenated into alcohol compounds under the action of catalysts. Preventing the aromatic products obtained during the depolymerization of lignin from being over-hydrogenated to form saturated compounds is also one of the current research difficulties. Previous studies have reported that in the same type of carbon-based catalysts, the larger the specific surface area of ​​the carbon carrier, the easier it is to induce the hydrogenation of the aromatic intermediates generated by the model compound. When the specific surface area is greater than 500m 2 / g carbon-based catalyst, phenolic compounds can be completely hydrogenated to cyclohexanol products. However, in the case of a small specific surface area (less than 100m 2 / g) of the carrier, the lignin model compound is difficult to convert well. 2 / g) of the carrier can achieve substrate conversion and inhibit the hydrogenation reaction of aromatic products. The hydrogenation of aromatic products can be avoided by selecting a suitable carrier to synthesize a specific catalyst. Compared with precious metals, the cost of metal Ni is lower; and among non-precious metals, Ni has stronger hydrogenation cracking performance. Some nickel-based catalysts are widely used in the depolymerization reaction of lignin and its derivatives. The moderate pore structure and specific surface area in gasification slag are conducive to the loading of metals. And during the reaction process, it can effectively avoid the excessive hydrogenation of aromatic products. How to load Ni on the catalyst prepared in gasification slag to catalyze the depolymerization of lignin to prepare aromatic products is a field worthy of study. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a coal gasification slag-loaded nickel-based catalyst and its application in the depolymerization of lignin or its derivatives. The method uses coal gasification slag as a carrier to synthesize a high-performance catalyst, and the catalyst is applied to the depolymerization of lignin or its derivatives with excellent application effect, is green and environmentally friendly, and has efficient economic and performance advantages in catalyzing the depolymerization of lignin to prepare aromatic products.

[0006] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:

[0007] A method for preparing a coal gasification slag-supported nickel-based catalyst, the specific steps are as follows:

[0008] Step 1, put 0.015325g-1.749g of the nickel-based compound into a beaker, add 2-20mL of deionized water, and stir with a glass rod until it is completely dissolved;

[0009] Step 2, add 0.1-2 g of CGS and continue stirring for 5-30 min to ensure that the metal precursor is highly dispersed on the carrier;

[0010] Step 3, the mixed solution is sealed with tin foil, and immersed in a vacuum drying oven at room temperature for 6-48 hours, and then dried;

[0011] Step 4, the obtained block solid is evenly ground with a mortar and put into a tubular furnace, and the solid powder is calcined and reduced in the tubular furnace. First, N2 is passed into the tube to exhaust the air inside the reactor. After calcination for 1-4 hours, N2 is switched to H2, and reduced for 2 hours at the same volume flow rate and the same temperature. After the reduction is completed, H2 is switched to N2. After natural cooling, vacuum drying is performed to obtain the coal gasification slag-loaded nickel-based catalyst.

[0012] As an improvement, the nickel-based compound in step 1 is nickel nitrate hexahydrate (Ni(NO3)2·6H2O), nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O), nickel chloride hexahydrate (NiCl2·6H2O) or nickel sulfate hexahydrate (NiSO4·6H2O).

[0013] As an improvement, the drying temperature in step 3 is 110° C. and the drying time is 4-12 hours.

[0014] As an improvement, the flow rate of N2 in step 4 is 20-80 mL / min.

[0015] As an improvement, the calcination temperature in step 4 is 450-550°C, and the heating rate is 1-15°C / min.

[0016] The catalyst prepared by the above preparation method is used for catalytic depolymerization of lignin or its derivatives.

[0017] As an improvement, the application includes the following steps: placing a lignin model compound or lignin, a coal gasification slag-loaded nickel-based catalyst and a solvent into an autoclave, purging the autoclave with nitrogen to remove the air in the autoclave, sealing the autoclave, and filling the autoclave with H2 or N2; then heating the autoclave to the desired reaction temperature, and after continuing the reaction, naturally cooling the autoclave to room temperature and releasing the pressure, filtering the reaction mixture to obtain a liquid product; and detecting the product by gas chromatography-mass spectrometry (GC-MS) and gas chromatograph (GC).

[0018] As an improvement, the reaction temperature is 180° C., the mass ratio of the lignin model compound or lignin to the coal gasification slag-loaded nickel-based catalyst is 5:2, and the solvent is isopropanol.

[0019] Beneficial effects:

[0020] Compared with the prior art, the preparation method of the coal gasification slag-loaded nickel-based catalyst and its application in the depolymerization of lignin or its derivatives of the present invention have the following advantages:

[0021] 1. Traditional CGS utilization methods will lead to soil pollution and waste of resources. The present invention has developed a new CGS application method, which uses CGS to catalytically depolymerize waste lignin and obtain high value-added aromatic compounds. This method is more environmentally friendly and more conducive to the subsequent large-scale application of CGS.

[0022] 2. The special porous structure of CGS can make the metal Ni evenly dispersed to synthesize a highly active catalyst. At the same time, the appropriate specific surface area in CGS can also effectively inhibit the hydrogenation of aromatic intermediates in the depolymerization process of lignin. The 10% Ni / CGS synthesized by the present invention can catalyze the depolymerization of lignin model compound benzyl phenyl ether under mild conditions (180°C, 1MPa H2) to obtain highly selective phenol and methylcyclohexane. Compared with traditional carbon-based and oxide-based catalysts, the catalyst has higher conversion efficiency for substrates and higher selectivity for aromatic products. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD spectrum of xNi / CGS prepared by the present invention;

[0024] Figure 2 The SEM spectra of xNi / CGS prepared in Example 1 of the present invention, (a) is the SEM spectrum of CGS, (b) is the SEM spectrum of 3% Ni / CGS, (c) is the SEM spectrum of 5% Ni / CGS, (d) is the SEM spectrum of 7% Ni / CGS, (e) is the SEM spectrum of 10% Ni / CGS, and (f) is the SEM spectrum of 15% Ni / CGS;

[0025] Figure 3 The TEM spectra of the catalysts prepared by the present invention at different ratios are shown in Figure 1, wherein (a) is the TEM spectrum of 3% Ni / CGS, (b) is the TEM spectrum of 5% Ni / CGS, and (c) is the TEM spectrum of 10% Ni / CGS;

[0026] Figure 4 The TEM spectra of the catalysts prepared by the present invention at different ratios are shown in FIG. 1 , wherein (a) is the TEM spectrum of 7% Ni / CGS, and (b) is the TEM spectrum of 15% Ni / CGS;

[0027] Figure 5 HRTEM spectrum of 10% Ni / CGS prepared in Example 1 of the present invention;

[0028] Figure 6 The effect of 10% Ni / CGS prepared in Example 1 of the present invention on the conversion of BPE at different reaction temperatures, reaction pressures, catalyst dosages and solvents;

[0029] Figure 7 Total ion current chromatograms obtained for non-catalyzed (a) and 10% Ni / CGS (b) depolymerization of lignin;

[0030] Figure 8The product distribution diagram of lignin depolymerization under non-catalytic (a) and 10% Ni / CGS (b), where 1 is phenols; 2 is ketones; 3 is cyclohexanols; 4 is aromatic hydrocarbons; 5 is cycloalkanes; 6 is aromatic ethers; 7 is esters; 8 is acids; and 9 is heteroatoms). DETAILED DESCRIPTION

[0031] The following examples will enable those skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0032] The coal gasification slag (CGS) used in the present invention was obtained from a coal gasification plant in Shaanxi Province, China. 2 A series of Ni-based catalysts with different loading amounts were synthesized by using CGS with % Ni / g as the carrier. The catalysts are named xNi / CGS, where x represents the actual loading amount of Ni. Taking 10% Ni / CGS as an example, the preparation steps of the catalyst of the present invention are described in detail.

[0033] Example 1

[0034] 0.1101g of nickel nitrate hexahydrate (Ni(NO3)2·6H2O) was placed in a beaker, 2mL of deionized water was added, and it was stirred with a glass rod until it was completely dissolved. Then 0.2g of CGS was added and stirred for 10min to ensure that the metal precursor was highly dispersed on the carrier. The mixed solution was then sealed with tin foil and impregnated in a vacuum oven at room temperature for 24h. After impregnation, it was taken out and placed in a 110℃ oven for 4h. The obtained block solid was evenly ground with a mortar and placed in a tube furnace. The solid powder was calcined and reduced in the tube furnace. First, N2 with a volume flow rate of 60mL / min was passed into the tube for 20min to exhaust the air inside the reactor, and then the temperature was increased from 30℃ to 450℃ at a heating rate of 10℃ / min, and calcined at 450℃ for 1-4h, and then the gas was switched to H2 and reduced at the same volume flow rate and temperature for 2h. After the reduction was completed, the tube was switched to 60 mL / min of N2. After the catalyst was cooled naturally, it was taken out and placed in a vacuum desiccator for later use, and was recorded as catalyst 10% Ni / CGS.

[0035] Example 2

[0036] Except that the added amount of Ni(NO3)2·6H2O is 0.03065 g, the rest is the same as Example 1, and is recorded as catalyst 3% Ni / CGS.

[0037] Example 3

[0038] Except that the added amount of Ni(NO3)2·6H2O was 0.05215 g, the rest was the same as Example 1, and was recorded as catalyst 5% Ni / CGS.

[0039] Example 4

[0040] Except that the added amount of Ni(NO3)2·6H2O was 0.0745 g, the rest was the same as Example 1, and was recorded as catalyst 7% Ni / CGS.

[0041] Example 5

[0042] Except that the added amount of Ni(NO3)2·6H2O was 0.1749 g, the rest was the same as Example 1, and was recorded as catalyst 15% Ni / CGS.

[0043] Table 1 Physical properties of catalysts with different loadings

[0044]

[0045] a The total specific surface area was calculated using the BET formula;

[0046] b The total pore volume was measured at a relative pressure of P / P0 = 0.99;

[0047] c The micropore specific surface area and micropore volume were calculated using the t method;

[0048] d The difference between the total specific surface area and the micropore surface area and the total pore volume and the micropore volume.

[0049] The pore structure characteristics of CGS and coal gasification slag supported nickel-based catalyst xNi / CGS are shown in Table 1. The specific surface area (SSA) of the original CGS is 233 m 2 / g, compared with traditional porous carbon materials, CGS has a lower specific surface area. Existing studies have shown that catalysts prepared from high specific surface area carbon can further hydrogenate aromatic products into cycloalkanes and alcohol compounds. In addition, by reducing the specific surface area of ​​the carrier, the hydrogenation of aromatic rings is avoided. However, on some oxide-based catalysts with very low specific surface areas (such as CeO2, WO3, etc.), the substrate cannot be converted well. Therefore, the moderate surface area in CGS can effectively promote the directional conversion of lignin derivatives to aromatic products, that is, the specific surface area of ​​micropores in CGS and catalysts is greater than the specific surface area of ​​mesopores. With the increase of Ni loading in CGS, the specific surface area of ​​the synthesized xNi / CGS begins to gradually decrease.

[0050] like Figure 1As shown, there is an obvious (002) C crystal plane peak in the XRD spectra of CGS and coal gasification slag loaded nickel-based catalysts. This confirms that the CGS obtained from the coal gasification process still retains part of the unburned carbon structure. It can also be observed from the XRD spectrum of CGS that the CGS structure is relatively pure, with almost no impurity peaks of other substances. After Ni is loaded in CGS, the XRD spectrum peak of Ni appears on the catalyst surface. In the XRD spectrum of xNi / CGS, the spectral peaks at 2θ of 44.6°, 52.0° and 76.6° are the (111), (200) and (220) crystal planes of Ni. When the nickel loading is low, the Ni (111) peak is almost invisible in the prepared 3% Ni / CGS. When the Ni loading is increased from 3% to 15%, the XRD peak of Ni begins to become clearly visible. The above analysis shows that metallic Ni has been successfully loaded into CGS.

[0051] like Figure 2 As shown in (a), the morphology of CGS is similar to that of traditional carbon supports, and there are many pores on the surface of CGS. After adding Ni to CGS, small round bright spots appear on the surface of the catalyst ( Figure 2 (b)-(f)). The small bright spots in the SEM spectra of the catalyst are metallic Ni. As the Ni loading increases, the distribution of bright spots in the catalyst becomes more obvious. SEM characterization can only be used to analyze the morphological characteristics of the sample, and TEM characterization is required to analyze the precise particle size of Ni.

[0052] like Figure 3 and Figure 4 As shown, the distribution of nickel particles in 3% Ni / CGS is relatively small compared with 5%-15% Ni / CGS. The average particle size of Ni in 5%-10% Ni / CGS is about 10nm. For 10% Ni / CGS, further increasing or decreasing the nickel loading will lead to an increase in the size of nickel particles. When the Ni loading is further increased to 15%, a large amount of Ni accumulates on the surface of CGS, resulting in an average particle size of Ni in 15% Ni / CGS as high as 15.8nm. The higher the nickel activity in the catalyst, the more obvious the trend of aromatic ring hydrogenation in the product. Under the premise of ensuring complete conversion of the reaction substrate, a lower metal loading is conducive to preventing hydrogenation of the aromatic ring of the intermediate product and reducing the cost of the reaction. The moderate nickel dispersion and metal active sites in the preferred 10% Ni / CGS of the present invention promote the catalytic conversion of lignin derivatives.

[0053] HRTEM spectrum of 10% Ni / CGS ( Figure 5) shows the lattice fringes of metallic Ni. The measurement results show that the lattice fringes spacing in Ni / CGS is 0.208nm, which is consistent with the Ni(111) crystal plane spacing. In addition, the SAED diffraction pattern of 10% Ni / CGS also shows that the Ni form in Ni / CGS is Ni(111) crystal. Only one Ni(111) crystal plane was found on the surface of Ni / CGS. This result is consistent with Figure 1 The XRD characterization is consistent with that of

[0054] Example 6

[0055] 50mg lignin or model compound benzyl phenyl ether (BPE), 10-50mg catalyst and 20mL of isopropyl alcohol are put into 100mL stainless steel autoclave and sealed.Then replace with hydrogen three times to exclude unnecessary air in reactor, and be filled with hydrogen (0.1-4MPa) of certain pressure.Temperature is set to the reaction temperature of expectation, and keeps certain time under the rotating speed of 300rpm.After reaction finishes, reactor is naturally cooled to room temperature and pressure relief.With filter, catalyst and liquid product are separated, and by gas chromatography-mass spectrometer (GC-MS) and gas chromatograph (GC) analyze liquid product.

[0056] Specifically, the lignin model compound (BPE) was subjected to catalytic hydrogenolysis reaction, and the specific reaction conditions were: 50 mg BPE, 20 mg catalyst, 1 MPaH2, 20 mL isopropanol, reaction temperature 180°C, and reaction time 2 h. The effects of different catalysts on the catalytic conversion of benzyl phenyl ether (BPE) are shown in Table 2.

[0057] Table 2 Effect of different catalysts on catalytic conversion of benzyl phenyl ether (BPE)

[0058]

[0059] In the above reaction system, BPE was not converted in the reaction system using CGS as a catalyst or without a catalyst. When a small amount of 3% metal Ni was loaded into CGS, 10.1% of BPE was converted into phenol and toluene on 3% Ni / CGS. This shows that metal Ni is the active site for the conversion of BPE. Ni serves as the active center of the catalyst, while CGS provides a loaded precursor for metal Ni. Ni / CGS prepared by combining Ni and CGS effectively promotes the conversion of BPE. As the loading amount of metal Ni in CGS gradually increases, the conversion rate of BPE gradually increases. Under the catalysis of 10% Ni / CGS, 100% of BPE was converted into phenol and toluene as the main target products. With the increase of nickel loading, the trend of phenol hydrogenation to prepare cyclohexanol also becomes obvious, but this is not conducive to the formation of aromatic ring compounds. On 15% Ni / CGS, 31.5% of phenol was hydrogenated to cyclohexanol, while no aromatic ring hydrogenation reaction occurred in toluene. In order to ensure the complete conversion of BPE and obtain high yields of phenol and toluene in this reaction, the optimal loading amount of nickel was determined to be 10%.

[0060] The structure of toluene is more stable than that of phenol, and the results show that it is difficult for the catalyst to hydrogenate toluene into methylcyclohexane. Some previous studies have also confirmed that phenol is easily hydrogenated into cyclohexanol, and it is difficult to obtain a high yield of phenol in the reaction system. The Ni-loaded CGS with an appropriate pore structure adsorbs an appropriate amount of hydrogen to generate active hydrogen species, which can not only promote the conversion of BPE, but also inhibit the hydrogenation of aromatic rings. No direct hydrogenation products of BPE aromatic rings were found during the entire reaction process. At the same time, the breakage of aliphatic CO bonds in BPE is the main reaction pathway, which is due to its lower bond energy compared with aromatic CO bonds. The fact that benzene and benzyl alcohol did not appear in the reaction system also confirms the above view. The present invention uses waste CGS generated in the coal gasification process as a carrier to synthesize a catalyst for the efficient depolymerization of lignin derivatives, which has certain research significance.

[0061] Example 7

[0062] The optimal conditions for BPE conversion were studied using 10% Ni / CGS as the best catalyst. Figure 6 As shown in (a), the conversion of BPE is 41% at a reaction temperature of 140°C, and increases to 84.8% when the temperature is increased to 160°C. At a reaction temperature of 180°C, BPE is completely cracked into 100% toluene and 87.1% phenol under the catalysis of 10% Ni / CGS.

[0063] As the temperature increases, the hydrogenation tendency of the aromatic ring in phenol increases. When the reaction temperature is increased to 200°C, 39.3% of phenol is hydrogenated to cyclohexanol. During the entire reaction process, toluene did not undergo further hydrogenation reaction. This further proves the structural stability of toluene. The increase in temperature is not only beneficial to the conversion of BPE, but also promotes the conversion of phenol. Taking into account factors such as reaction cost, the optimal reaction temperature for BPE cracking in this system is determined to be 180°C.

[0064] Example 8

[0065] Effect of H2 pressure on BPE cracking Figure 6 (b). After adding 0.1MPa of hydrogen to the reactor, the conversion of BPE was 79.3%. At the same time, 7.8% of phenol was hydrogenated to form cyclohexanol. With the increase of H2 pressure, the conversion of BPE and the hydrogenation selectivity of phenol increased. At an initial H2 pressure of 1MPa, 100% of BPE was cracked into 100% toluene and 87.1% phenol. When the reaction pressure was increased to 2MPa, the yield of toluene in the product remained at 100%, while the yield of phenol gradually decreased.

[0066] Although in the prior art, a small amount of BPE also undergoes direct hydrogenation of aromatic rings under high pressure, this is not conducive to the direct cleavage of the CO bond in BPE. From the above results, it can be seen that in the present invention, no direct BPE hydrogenation product is detected even when the reaction pressure reaches 2MPa. This further confirms that the Ni / CGS catalyst has an excellent CO bond cleavage advantage.

[0067] Example 9

[0068] like Figure 6 As shown in (c), when the ratio of substrate BPE to catalyst is 5:1, 40.2% of BPE is broken into target products phenol and toluene. When the amount of catalyst is increased to 20 mg, BPE is completely depolymerized into toluene, phenol and a small amount of cyclohexanol. The increase of Ni active sites in the catalyst can promote substrate conversion and hydrogenation of aromatic rings. It can be seen that starting from 20 mg, as the amount of catalyst increases, the proportion of cyclohexanol produced by hydrogenation of phenol gradually increases.

[0069] In summary, the optimal dosage of 10% Ni / CGS catalyst is 20 mg, that is, the dosage ratio of reactant to catalyst is 5:2. The ratio of reactant to nickel-based and other non-precious metal catalysts used in previous studies is 5:3, 2:1 or even 1:1, while the ratio of reaction substrate to catalyst used in the present invention is relatively high, and the amount of catalyst used is small. Therefore, the present invention has great subsequent application prospects.

[0070] Example 10

[0071] Effect of reaction solvent on BPE conversion Figure 6 (d) as shown.

[0072] When the reaction system is carried out under primary alcohols (such as methanol and ethanol), BPE cannot be converted. With isopropanol as solvent, 84.8% of BPE is converted into phenol and toluene under the reaction conditions of 160°C. However, when ordinary alcohols are used as reaction solvents, the conversion efficiency of BPE varies greatly. There are two main reasons for this result. On the one hand, secondary alcohol isopropanol is easier to remove hydrogen atoms in the structure to form active hydrogen than primary alcohols. On the other hand, it is due to the different solubility of H2 in solvents. Active hydrogen is necessary for the breaking of CO bonds in BPE. The rapid dissolution of hydrogen in isopropanol produces a large amount of active hydrogen, which promotes the cracking of BPE. In the combination of hydrogen and n-hexane solvent, the hydrogenation capacity of phenol is improved, which further proves that the catalysis of the present invention is effective.

[0073] Embodiment 11

[0074] The 10% Ni / CGS prepared in Example 1 was used to catalyze hydrogenation and depolymerization of lignin, wherein the reaction conditions were: 50 mg lignin, 4 MPaH2, 10 mL isopropanol, 280°C, 6 h, 50 mg catalyst, wherein no catalyst was added to the reaction system for comparison. The results are shown in Table 3.

[0075] Table 3 Conversion of lignin depolymerization under non-catalytic and 10% Ni / CGS conditions

[0076]

[0077] It can be seen from Table 3 that under the reaction conditions of 280°C and 6h, the lignin conversion rate was 39.6% without the participation of catalyst in the reaction. Under the same reaction conditions, after adding 10% Ni / CGS catalyst to the system, the lignin conversion rate increased to 61.1%. This shows that 10% Ni / CGS plays a vital role in the depolymerization process of lignin.

[0078] Figure 7 The GC-MS spectrum of the liquid product obtained after lignin conversion. As can be seen from the figure, most of the lignin conversion products are phenolic compounds, such as guaiacol, 4-methylguaiacol and 4-ethylguaiacol. Due to the complexity of lignin depolymerization products (100-200 types), lignin depolymerization products are divided into 9 categories, such as Figure 8 In the non-catalytic system, the proportion of phenolic products is 76.4%. When Ni / CGS catalyst is applied to the system, the proportion of phenolic products decreases, and phenolic compounds are gradually hydrogenated into ketones and alcohols.

[0079] The results showed that the reaction pathway of lignin was basically the same as that of the model compound. The abundant CO bonds in lignin were depolymerized to produce a large amount of phenols. The structure of the aromatic phenolic compounds in the lignin depolymerization products was also well preserved on Ni / CGS.

Claims

1. A method for preparing a coal gasification slag-supported nickel-based catalyst, characterized in that: The specific steps are as follows: Step 1, put 0.015325g-1.749g of the nickel-based compound into a beaker, add 2-20mL of deionized water, and stir with a glass rod until it is completely dissolved; Step 2, add 0.1-2 g of CGS and continue stirring for 5-30 min to ensure that the metal precursor is highly dispersed on the carrier; Step 3, the mixed solution is sealed with tin foil, and immersed in a vacuum drying oven at room temperature for 6-48 hours, and then dried; Step 4, the obtained block solid is evenly ground with a mortar and put into a tubular furnace, and the solid powder is calcined and reduced in the tubular furnace. First, N2 is passed into the tube to exhaust the air inside the reactor. After calcination for 1-4 hours, N2 is switched to H2, and reduced for 2-4 hours at the same volume flow rate and the same temperature. After the reduction is completed, H2 is switched to N2. After natural cooling, vacuum drying is performed to obtain the coal gasification slag-loaded nickel-based catalyst.

2. The method for preparing a coal gasification slag-supported nickel-based catalyst according to claim 1, characterized in that: The nickel-based compound in step 1 is nickel nitrate hexahydrate, nickel acetate tetrahydrate, nickel chloride hexahydrate or nickel sulfate hexahydrate.

3. The method for preparing a coal gasification slag-supported nickel-based catalyst according to claim 1, characterized in that: The drying temperature in step 3 is 110° C. and the drying time is 4-12 hours.

4. The method for preparing a coal gasification slag-supported nickel-based catalyst according to claim 1, characterized in that: The flow rate of N2 in step 4 is 20-80 mL / min.

5. The method for preparing a coal gasification slag-supported nickel-based catalyst according to claim 1, characterized in that: The calcination temperature in step 4 is 450-550°C, and the heating rate is 1-15°C / min.

6. Use of the catalyst prepared by the preparation method according to claim 1 in catalytic depolymerization of lignin or its derivatives.

7. The use according to claim 6, characterized in that: The following steps are involved: A lignin model compound or lignin, a coal gasification slag-loaded nickel-based catalyst and a solvent are placed in an autoclave, the autoclave is purged with nitrogen to remove the air in the autoclave, the autoclave is sealed, and H2 or N2 is filled into the autoclave; the autoclave is then heated to a desired reaction temperature, and after the reaction is continued, the autoclave is naturally cooled to room temperature and the pressure is released, and the reaction mixture is filtered to obtain a liquid product; the product is detected by a gas chromatography-mass spectrometer and a gas chromatograph.

8. The use according to claim 7, characterized in that: The reaction temperature is 180° C., the mass ratio of the lignin model compound or lignin to the coal gasification slag-loaded nickel-based catalyst is 5:2, and the solvent is isopropanol.